2018
DOI: 10.1007/s11916-018-0687-3
|View full text |Cite
|
Sign up to set email alerts
|

Pain, Headache, and Other Non-motor Symptoms in Myasthenia Gravis

Abstract: Work in this area has been limited. Recent studies have identified bodily pain and headache as common complaints in patients with MG. A growing literature also suggests that there may be an association of MG and sleep disturbance (both obstructive sleep apnea and sleep cycle dysfunction). Few studies suggest some measurable abnormalities of olfaction, gustation, audition, and autonomic function. The cognitive and psychosocial aspects of MG represent an emerging area of clinical and research interest, but large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…In a retrospective study of 184 Myasthenia patients, tension-type headache is reported in 38.6% and migraine headache in 4.9%. 14 The limitations of our study are, the cohort is only from our emergency department, and we are unaware of the true extent of the misdiagnosis. Also, we cannot entirely rule out the overlapping vascular events at the time of presentation, which makes the diagnosis complicated.…”
Section: Discussionmentioning
confidence: 93%
“…In a retrospective study of 184 Myasthenia patients, tension-type headache is reported in 38.6% and migraine headache in 4.9%. 14 The limitations of our study are, the cohort is only from our emergency department, and we are unaware of the true extent of the misdiagnosis. Also, we cannot entirely rule out the overlapping vascular events at the time of presentation, which makes the diagnosis complicated.…”
Section: Discussionmentioning
confidence: 93%
“…Tension-type headache in MG is associated with diplopia and ptosis [36] . Some of the immunosuppressive drugs used in MG can have headache as a side-effect [35] . Opiates for severe pain can lead to a respiratory depression unwanted in MG.…”
Section: Daily Symptomsmentioning
confidence: 99%
“…Some MG patients report physical and cognitive fatigue with reduced cognitive ability and impaired social and physical functions. Such reports illustrate the patient perspective but do not necessarily imply a true cognitive impairment due to brain dysfunction [35] . Preliminary patient reports and experimental data may indicate cerebral involvement in MuSK MG [48] .MG should be regarded as a disease not affecting the brain, but it should be acknowledged that some…”
Section: Cognitive Functionmentioning
confidence: 99%
“…Myasthenia gravis is an autoimmune disorder which presents a series of clinical manifestations which are generally motor, but there have been documented cases of patients with myasthenia gravis that presented non motor symptoms [1]. The hallmark of the disorder is muscle weakness, which typically worsens during physical exercise and improves upon rest [2,3].…”
Section: Abstract: Myasthenia Gravis Achr-ab Thymectomy Acetylcholinementioning
confidence: 99%